2017
DOI: 10.1136/bcr-2016-216809
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pregnancy in a primigravida with uncorrected Pentalogy of Fallot

Abstract: Pentalogy of Fallot is a cyanotic congenital heart disease that has guarded prognosis without surgical intervention in infancy. Women with uncorrected defects rarely survive into childbearing age and pregnancy in this group is associated with a high rate of perinatal loss. Physiological cardiovascular changes in pregnancy can lead to maternal haemodynamic instability with subsequent adverse cardiac sequelae with or without fetal decompensation. Optimum management and pregnancy outcomes in mother with uncorrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This is, to our knowledge, one of the few cases reported of a successful pregnancy in women with PoF without surgical repair [ 5 , 6 ]. It shows that it is possible, but it is not risk-free.…”
Section: Discussionmentioning
confidence: 99%
“…This is, to our knowledge, one of the few cases reported of a successful pregnancy in women with PoF without surgical repair [ 5 , 6 ]. It shows that it is possible, but it is not risk-free.…”
Section: Discussionmentioning
confidence: 99%
“…Since pregnancy introduces extra load on the heart, and can damage cardiac functions, resulting in the increase in both maternal and perinatal morbidity [4,5]. Previous studies have demonstrated that cardiac and obstetric complications are more likely to occur in patients without surgical repair [6][7][8]. The most common cardiac complications include progressive dilatation of the right ventricle and ventricular failure, thromboembolism, atrial and ventricular arrhythmias, progressive aortic root dilatation and endocarditis [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Without repair, TOF patients rarely reach childbearing age and get pregnant. Since pregnancy introduces extra load on the heart, and can damage cardiac functions, resulting in the increase in both maternal and perinatal morbidity [4,5].Previous studies have demonstrated that cardiac and obstetric complications are more likely to occur in patients without surgical repair [6][7][8]. The most common cardiac complications include progressive dilatation of the right ventricle and ventricular failure, thromboembolism, atrial and ventricular arrhythmias, progressive aortic root dilatation and endocarditis [1,9].…”
Section: Introductionmentioning
confidence: 99%